Optimizing Sales With Social Media at UD. Sumber Kacang Pace Nganjuk - Maulidan, Abiyyu Pradila; Fauji, Diah Ayu Septi (Universitas Nusantara PGRI Kediri, 2025)
Research objectives: The purpose of this study is to analyze the use of social media to increase sales and create synergies between digital marketing and conventional marketing. Method: In this study, the researcher used a descriptive qualitative method. With interview, observation, and documentation techniques. The study of this object is UD. Sumber Kacang at RT 024 RW 009 Gondang Village, Pace District, Nganjuk Regency. Research Findings: The use of various social media (Facebook, Instagram, TikTok, WhatsApp), the seriousness of the use of social media, the selection of the right time for posting, and the consistency of posting content on social media. Theoretical contribution/Originality: The contribution of this research theoretically strengthens the theory of digital marketing and the theory of promotion strategy. Implications of Practice / Policy: Practically, the results of this study can be adapted by similar entrepreneurs to be able to use the social media used by companies such as Facebook, TikTok, Instagram, and Whatsapp effectively. Research limitations: The limitation of this study is the duration of the research which makes the scope of the analysis limited. Keywords: social media, sales optimization, digital marketing